(untitled) (Arquivo Maaravi: Revista Digital de Estudos Judaicos da UFMG, 2020)
In his 2017 documentary The Impure Daniel Najenson straddles the notions of past and present to denounce the horrors and the injustice of sex trafficking in Argentina. Following a family tale of a great-aunt who migrated from Eastern Europe to South America at the beginning of the twentieth century, he digs deep into Israeli and Argentine archives to tell the story of the Zwi Migdal and the way Jewish women were forced into prostitution. To give voice to these women, he brings in Sonia Sánchez, originally from northern Argentina, and forced into prostitution in Buenos Aires when she was seventeen years old. Sánchez tells her own story, but also reads letters from the now deceased victims of sex trade a century ago. This self-professed feminist and activist is also shown in demonstrations and interviews fueling the NiUnaMenos movement in Argentina, while the #MeToo and TimesUp movements explode in the U.S.